2021
DOI: 10.1016/j.waojou.2021.100538
|View full text |Cite
|
Sign up to set email alerts
|

Decreasing ten-year (2008–2018) trends of the prevalence of childhood asthma and air pollution in Southern Taiwan

Abstract: Background Asthma is a common pediatric chronic respiratory disease worldwide. Previous studies showed the prevalence of childhood asthma increased in developed countries as well as in Taiwan in the late 20th century. Recently, several reports from different parts of the world showed a reversed trend in this epidemic of childhood asthma prevalence. This study investigated the trend of childhood asthma through serial cross-section questionnaire surveys in the southern part of Taiwan, and identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 28 publications
1
7
1
Order By: Relevance
“…19 Similarly, a study conducted in southern Taiwan showed a decline in the prevalence of asthma symptoms as doctor diagnosis, exercise-induced wheeze and nocturnal cough. 20 However, contrary to our results, many studies suggest a continued increase in asthma prevalence, especially in LMICs. 21 In Ecuador, several studies conducted in different cities have estimated the prevalence of asthma and other RAD.…”
Section: Discussioncontrasting
confidence: 99%
“…19 Similarly, a study conducted in southern Taiwan showed a decline in the prevalence of asthma symptoms as doctor diagnosis, exercise-induced wheeze and nocturnal cough. 20 However, contrary to our results, many studies suggest a continued increase in asthma prevalence, especially in LMICs. 21 In Ecuador, several studies conducted in different cities have estimated the prevalence of asthma and other RAD.…”
Section: Discussioncontrasting
confidence: 99%
“…In the last few years, a number of reports from several countries have evaluated the time trends of major atopic diseases by analyzing at least 3 different time-points. 36 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 As can be seen in the Supplementary Fig. 4 , in general terms their results are in agreement with ours in the sense that the frequency of these diseases appear to be decreasing in recent years.…”
Section: Discussionsupporting
confidence: 89%
“…Compared with the 2010 survey, the prevalence of children’s respiratory diseases in the 2019 survey was decreased (shown in Table 3 and Figure 1), especially in urban areas, consistent with some other studies. 43,44 Boys and children with a family history of allergies have a higher prevalence. The prevalence of children’s respiratory diseases and allergic diseases in Shanghai is generally higher.…”
Section: Discussionmentioning
confidence: 99%